PENGARUH KNOWLEDGE MANAGEMENT DAN STRATEGIC PARTNER HUMAN RESOURCES TERHADAP PERENCANAAN STRATEGIK DAN KINERJA ORGANISASI (STUDI PADA LOCAL COMPANY INTERNET SERVICE PROVIDER DI MALANG) - Endriana, Yuni; Arifin, Zainul; Handayani, Siti Ragil (FIA UB, 2014)
The purpose of this study was to test the effect of knowledge management and the human resources department ( HR ) as a strategic partner in strategic planning and organizational performance. Studies conducted in the internet service provider in the city of Malang. The results prove the knowledge management and the HR department as a strategic partner that is good and right can improve the accuracy of strategic planning, and strategic planning to improve organizational performance. Knowledge management does not directly affect the performance of the organization, but it proves that the perfect strategic planning mediate the effect of knowledge management on organizational performance. This suggests that knowledge management is not a direct determinant of the performance of the organization, but its existence became an important input from the strategic planning process in an effort to improve organizational performance. Department of Human Resources as a strategic partner also does not directly affect the performance of the organization and strategic planning proved perfectly mediate HR strategic partner relationship with organizational performance. This illustrates that the involvement of the Department of Human Resources as a strategic partner not a direct determinant of organizational performance, but the ability of the HR department as a source of strategic planning for the organization, in an effort to improve organizational performance. Based on these results that strategic planning is based on knowledge management and HR department acts as a strategic partner can be a strategic capability. Keywords : Knowledge Management, Strategic Partner Human Resource, Strategic Planning, Organizational Performance Â Tujuan dari penelitian ini adalah untuk menguji pengaruh manajemen pengetahuan dan departemen sumber daya manusia (SDM) sebagai mitra strategis dalam perencanaan strategis dan kinerja organisasi. Studi yang dilakukan di penyedia layanan internet di kota Malang. Hasilnya membuktikan manajemen pengetahuan dan departemen SDM sebagai mitra strategis yang baik dan tepat dapat meningkatkan akurasi perencanaan strategis, dan perencanaan strategis dapat meningkatkan kinerja organisasi. Manajemen pengetahuan tidak secara langsung mempengaruhi kinerja organisasi, tetapi membuktikan bahwa perencanaan strategis memediasi secara sempurna pengaruh manajemen pengetahuan pada kinerja organisasi. Ini menunjukkan bahwa manajemen pengetahuan bukanlah penentu langsung dari kinerja organisasi, namun keberadaannya menjadi masukan penting dari proses perencanaan strategis dalam upaya meningkatkan kinerja organisasi. Departemen SDM sebagai mitra strategis juga tidak secara langsung mempengaruhi kinerja organisasi dan perencanaan strategis terbukti memediasi secara sempurnaÂ hubungan mitra strategis SDM dengan kinerja organisasi. Hal ini menggambarkan bahwa keterlibatan Departemen SDM sebagai mitra strategis bukan penentu langsung dari kinerja organisasi, namun kemampuan departemen SDM sebagai Â sumber organisasi untuk melakukan perencanaan strategis, dalam upaya untuk meningkatkan kinerja organisasi. Berdasarkan hasil ini bahwa perencanaan strategis didasarkan pada pengetahuan manajemen dan departemen SDM berperan sebagai mitra strategis dapat menjadi kemampuan strategis. Kata kunci : Manajemen Pengetahuan , Mitra Strategis Sumber Daya Manusia, Perencanaan Strategis , Kinerja Organisasi